Microstructural Consequences of Blast Lung Injury Characterized with Digital Volume Correlation - Arora, Hari; Nila, Alex; Vitharana, Kalpani; Sherwood, Joseph M.; Nguyen, Thuy-Tien N.; Karunaratne, Angelo; Mohammed, Idris K.; Bodey, Andrew J.; Hellyer, Peter J.; Overby, Darryl R.; Schroter, Robert C.; Hollis, Dave (Frontiers in Materials, 2017)
This study focuses on microstructural changes that occur within the mammalian lung when subject to blast and how these changes influence strain distributions within the tissue. Shock tube experiments were performed to generate the blast injured specimens (cadaveric Sprague-Dawley rats). Blast overpressures of 100 kPa and 180 kPa were studied. Synchrotron tomography imaging was used to capture volumetric image data of lungs. Specimens were ventilated using a custom-built system to study multiple inflation pressures during each tomography scan. This data enabled the first digital volume correlation (DVC) measurements in lung tissue to be performed. Quantitative analysis was performed to describe the damaged architecture of the lung. No clear changes in the microstructure of the tissue morphology were observed due to controlled low to moderate level blast exposure. However, significant focal sites of injury were observed using DVC, which allowed detection of bias and concentration in the patterns of strain level. Morphological analysis corroborated the findings, illustrating that the focal damage caused by a blast can give rise to diffuse influence across the tissue. It is important to characterise the non-instantly fatal doses of blast, given the transient nature of blast lung in the clinical setting. This research has highlighted the need for better understanding of focal injury and its zone of influence (alveolar inter-dependency and neighbouring tissue burden as a result of focal injury). Digital volume correlation techniques show great promise as a tool to advance this endeavour, providing a new perspective on lung mechanics post-blast.